Empirical estimation of the climatic representativeness in two different areas: desert and Mediterranean climates. (September 2017) - Soutullo, S.; Sánchez, M.N.; Enríquez, R.; Jimenez, M.J.; Heras, M.R.
Abstract: This paper develops a method, based on the PASCOOL methodology, to evaluate empirically the climatic representativeness of two Spanish locations in different meteorological zones: semi-arid and Mediterranean climates. New Typical Meteorological Years (TMYs) have been created using 10 years of measurement of the principal meteorological variables. Different weighting factors for the computed variables have been considered. The selected TMYs have been obtained minimizing the standard deviation with reference climatic databases of the studied locations and considering the final use of these files. With these assumptions, ambient temperature and global solar radiations have been estimated with the highest weighting factors.